KAP SURVEY ON SALIVARY DIAGNOSTIC METHODS OF CARIES RISK ASSESSMENT (Journal of Pharmaceutical Negative Results, 2022)
OBJECTIVE: Caries risk assessment is a tooth to evaluate the risk factors that are responsible for the occurrence of dental caries. Saliva is readily available and has been recognized in the diagnostics and normal health surveillance.MATERIALS AND METHODS: A convenient sample size of one hundred consecutive respondents participated in this study. A cross-sectional study was conducted using google forms and multiple-choice questions. The approval was obtained from the Institutional Ethics Committee. The questionnaire contained 12 questions based on the knowledge, awareness, attitude, and practice of dental interns and postgraduates towards salivary diagnostic methods for caries risk assessment. RESULTS: Out of the total study population, 52% of the participants were aware of caries risk assessment and 64% thought caries risk assessment is needed. About 89% of the participants knew how saliva is used as a diagnostic tool.CONCLUSION: More dental education programs have to be conducted to increase the awareness of salivary diagnostic aids for caries detection.